Development and Performance Validation of an Indirect Continuously Variable Transmission - Tang Zhirong; Ji Jie; Chen Peng; Shu Xin (Jixie chuandong)
Comparing with traditional pulley transmissions,a new configuration of indirect Continuously Variable Transmissions（CVT） is proposed to enhance the driving torque and reduce the complexity of control logic. The proposed indirect CVT is designed to provide continuous variations in the transmission ratio and switch the output speed direction without reverse-gear device. In order to verify the performance of the proposed indirect CVT,Solidworks software is employed to build the complete 3D geometric model. Moreover,the transfer characteristics of indirect CVT are analyzed by using Simscape/Driveline Toolbox and the designed transmission test-bed. The simulation and experimental results prove that,the kinetics and dynamics performance of the proposed indirect CVT are consistent with theoretical analysis.